Implementasi Kebijakan Merdeka Belajar-Kampus Merdeka di Era Covid-19 - Saputra, Abdurrahman; Setiawan, Farid; Djaka, Cahya Tri; Ridha, Dian Sekar Mei; Azzahra, Nabiila; Nurjanah, Putria Wati; Gimnastiar, Adli (Lembaga Yasin AlSys, 2022)
The writing of this article focuses on implementation of the free college policy of the covid-19 era. The method used in writing this article is qualitative with the approach to literature studies, that is, by collecting data from the various references that follow. This article explains how the implementation of independent home-study policy was during the covid-19 pandemic. Independent college programs have been established with the effort to establish competent graduate competence not only in expertise but also in morals and ethics. The policies of the program are also intended to assist schools affected by the covid-19 pandemic. In addition, it can help teachers carry out the learning process in schools where there is a shortage of qualified educators in technology and literacy.